Criteria for differentiating left bundle branch pacing and left ventricular septal pacing: A systematic review - Zhu, Kailun; Li, Linlin; Liu, Jianghai; Chang, Dong; Li, Qiang (Frontiers in Cardiovascular Medicine, 2022)
Background: As a novel physiological pacing technique, left bundle branch pacing (LBBP) can preserve the left ventricular (LV) electrical and mechanical synchronization by directly capturing left bundle branch (LBB). Approximately 60% to 90% of LBBP were confirmed to have captured LBB during implantation, implying that up to one-third of LBBP is actually left ventricular septal pacing (LVSP). LBB capture is critical for distinguishing LBBP from LVSP. Methods and results: A total of 15 articles were included in the analysis by searching PubMed, EMBASE, Web of Science, and the Cochrane Library database till August 2022. Comparisons of paced QRS duration between LVSP and LBBP have not been uniformly concluded, but the stimulus artifact to LV activation time in lead V5 or V6 (Stim-LVAT) was shorter in LBBP than LVSP in all studies. Stim-LVAT was used to determine LBB capture with a sensitivity of 76% to 95.2% and specificity of 78.8% to 100%, which varied across patient populations. Conclusion: The output‐dependent QRS transition from non-selective LBBP to selective LBBP or LVSP is direct evidence of LBB capture. LBB potential combined with short Stim-LVAT can predict LBB capture better. Personalized criteria rather than a fixed value of STIM-LVAT are necessary to confirm LBB capture in different populations, especially in patients with LBB block or heart failure.